Pengaruh Strategi Komunikasi Pemasaran Terpadu Somethinc terhadap Minat Beli Konsumen - Riha Anisah Aryahyah; Zulfebriges (Bandung Conference Series: Communication Management, 2023)
Abstract. This study aims to find out: (1) the influence of Somethinc’s integrated marketing communication strategi on customer’s buying interest, (2) the influence of Somethinc’s advertising on customer’s buying interest, (3) the influence of Somethinc’s sales promotion on customer’s buying interest, (4) the influence of Somethinc’s online marketing on customer’s buying interest, (5) the influence of Somethinc’s personal selling on customer’s buying interest. The population in this study are followers of @somethincofficial Instagram account. The sample taken in this study are 100 respondents, using random probability sampling technique from the questionnaire that was distributed. The method used in this study is a double linear regression analysis to measure the influence of more than one independent variable and one dependent variable. This research shows that: (1) Somethinc’s integrated marketing communication strategy has a significant influence on customer’s buying interest, (2) Somethinc’s advertising has a positive and most significant influence on customer’s buying interest, (3) Somethinc’s sales promotion has a positive but not quiet significant influence on customer’s buying interest, (4) Somethinc’s online marketing has a positive but not quiet significant influence on customer’s buying interest, (5) Somethinc’s personal selling has a positive but not quiet significant influence on customer’s buying interest. Abstrak. Penelitian ini bertujuan untuk mengetahui: (1) pengaruh strategi komunikasi pemasaran terpadu Somethinc terhadap minat beli konsumen, (2) pengaruh advertising Somethinc terhadap minat beli konsumen, (3) pengaruh sales promotion Somethinc terhadap minat beli konsumen, (4) pengaruh online marketing Somethinc terhadap minat beli konsumen, (5) pengaruh personal selling Somethinc terhadap minat beli konsumen. Populasi dalam penelitian ini adalah pengikut atau followers akun Instagram @somethincofficial. Sampel yang diambil sekitar 100 orang responden dengan teknik random sampling dari kuesioner yang telah disebarkan. Metode yang digunakan dalam penelitian ini adalah analisis regresi linear berganda untuk mengukur pengaruh dari lebih dari satu variabel bebas dan satu variabel terikat. Hasil penelitian menunjukkan bahwa: (1) strategi komunikasi pemasaran terpadu Somethinc berpengaruh signifikan terhadap minat beli konsumen, (2) advertising Somethinc berpengaruh positif dan paling signifikan terhadap minat beli konsumen, (3) sales promotion Somethinc berpengaruh positif namun tidak signifikan terhadap minat beli konsumen, (4) online marketing Somethinc berpengaruh positif namun tidak signifikan terhadap minat beli konsumen, (5) personal selling Somethinc berpengaruh positif namun tidak signifikan terhadap minat beli konsumen.